The Gap Analysis and Measurement of Customer Satisfaction in the Delivery of Services in Isfahan Province Gas Company Based on Parasuraman Model - Abdol Ali Keshtegar (Journal of Global Pharma Technology, 2018)
One of the indicators of efficiency of administrative system in developed countries is improving the quality of services offered to the citizens. One of the appreciable indices of public satisfaction is customer’s satisfaction with the delivery of services by the same organizations.This research’s design is to fulfil the intentions of the companies, which is to obtain the relative satisfaction and to receive valuable feedbacks of subscribers. The methodology of this study is surveyand is conducted as an applied research. The population of this study consisted of all households covered by the gas company in Isfahan province, which is equal to 191152 households. Sampling in this study is random cluster sampling and questionnaire and library resources are two major methods which are used to gather information and data. Statistical methods and data analysis methods to measure customer satisfaction are CSM,descriptive and inferential statistics using SPSS, and performing adaptive comparisons of the results obtained fromthe homes and offices and results of honoring client. Some of the main questions raised in this research are: optimum level of service received from Isfahan Province Gas Company and the average satisfaction with the service received? Time span of receiving service of Isfahan Province Gas Company (in minutes or days) and consistence with the standard time to service delivery? After the necessary calculations results were as follows: The results showed that in the majority of cases, the provision of services by the gas company is proportional to the standard time. Due to the lack of familiarity with the standards of work time, in most cases it is possible that the services provided in standard time be realized, but the customer satisfaction with the service received is still not so high.Keywords: Satisfaction, service recipients, Isfahan Province Gas Company, CSM.